The Man in the Background: The Search for Maecenas. (2020) - Ridley, Ronald T.
Abstract: Since the late sixteenth century parts of the 'imperial frieze' of the Ara Pacis have been known. The most striking figure in the background of the southern frieze is that long thought to be a portrait of Maecenas, the Etruscan prince and literary patron of the Augustan era. This article attempts three things: to discover 1. Where and how this identification originated, 2. What evidence there now is for that identification, and 3. What alternative identifications can be offered. The bibliography is substantial, the trail is complicated and highly paradoxical, and fantasy has often played a large role. The 'evidence' in play for centuries has sometimes evaporated into thin air. The identities proposed are, in fact, numerous. Not of least interest is the hidden or mistaken identity, in turn, of crucial modern scholars. A method is proposed at last for evaluating the identifications of this background portrait, including obvious comparison with other background figures. This analysis emphasizes how much is still not known about the most famous piece of Augustan art. An attempt is nevertheless made in the last analysis, to support what can be offered, in the light of current understanding, as the most plausible identification.